Educational policies of teacher formation in focus: Changes and continuities - Elvira Cristina Martins Tassoni; Camila Mattos dos Reis (Arizona State University, 2018)
This article discusses two program proposals for education literacy teachers that are part of two different educational policies in Brazil: the National Pact for Literacy in the Right Age (Pacto Nacional pela Alfabetização na Idade Certa - PNAIC) - from Federal Government - and the Reading and Writing Program (Programa Ler e Escrever) - from the state of São Paulo. The research, developed through a documentary analysis, aims to investigate the main differences between these proposals for the continuing education of literacy teachers. The analysis centers on official documents that regulate both the PNAIC and the Reading and Writing Program, accessed through the official websites of each program and research conducted on the Reading and Writing Program. The study identified the two proposals' principles and how they are implemented. The results allowed the analysis of the two programs according to three fundamental axis's for the continuing education of literacy teachers: the proposed forming model; the central figure of the formative network; and the organization of pedagogical work with the mother tongue. This research provides evidence for the comprehension of the advances, continuities and setbacks in the current trends of policies for the continuing education of literacy teachers in Brazil.